Long-Term Strength of Porous Geomaterials by a Micromechanical Model considering Alternate Wetting and Drying Condition. (8th February 2021) - Zhang, Jin; Fu, Shirong; Ni, Tao; Han, Bei; Shi, Chong
Abstract : This study is devoted to determining the long-term strength of porous geomaterials under alternate wetting and drying condition by statical shakedown analysis. In the framework of micromechanics of porous materials, Gurson's hollow sphere model with Drucker-Prager solid matrix is adopted as the representative volume element. The effects of alternate wetting and drying are considered as variable water pressure imposed on the inner boundary surface of the unit cell. The cyclic responses are separated as a pure hydrostatic part under compressive/tensive loads and an additional deviatoric part to capture shear effects. The reduction of the long-term strength due to inner water pressure is observed by the illustration of obtained macroscopic criteria with respect to various load parameters. In addition, the accuracy of the analytical solution is also verified by comparing to the results of FEM-based step-by-step computations.